2023
DOI: 10.1002/adsu.202300179
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical Plasticization of Fruits and Vegetables Processing Byproducts for the Preparation of Bioplastics

Abstract: Byproducts of the processing of foods are usually non‐edible residues that are typically discarded, even though they contain large amounts of natural polymers with great potential in bioplastics and biocomposites preparation. Herein, a new method of production of vegetable‐waste‐derived biocomposites is developed. It consists of the thermomechanical processing of different residues in the presence of small amounts of water, representing an advancement in the state‐of‐the‐art in the complete conversion of fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Another reason is the hydrophilic nature of lignocellulosic components, which are also found in EAP [ 67 ]. For comparison, biocomposites made from pomace such as residues from the processing of carrots, oranges, or spinach, at maximum air saturation with water vapor RH 100%, absorbed up to 40–60% of moisture from the air [ 68 ]. Referring to the results obtained and the research of other authors, it can be concluded that materials made from extruded (EAP) apple pomace and (SP) starch should not be subjected to hourlong exposure to high-air-humidity conditions, RH 75, 90%.…”
Section: Resultsmentioning
confidence: 99%
“…Another reason is the hydrophilic nature of lignocellulosic components, which are also found in EAP [ 67 ]. For comparison, biocomposites made from pomace such as residues from the processing of carrots, oranges, or spinach, at maximum air saturation with water vapor RH 100%, absorbed up to 40–60% of moisture from the air [ 68 ]. Referring to the results obtained and the research of other authors, it can be concluded that materials made from extruded (EAP) apple pomace and (SP) starch should not be subjected to hourlong exposure to high-air-humidity conditions, RH 75, 90%.…”
Section: Resultsmentioning
confidence: 99%